From laboratory scale to innovative spruce-based biorefinery. Note II: Preliminary techno-economic assessment - Gilardi, Matteo; Bisotti, Filippo; Berglihn, Olaf T.; Tschentscher, Roman; Hansen, Line D.; Horn, Svein J.; Várnai, Anikó; Wittgens, Bernd (Computer Aided Chemical Engineering, 2024)
This work shows a preliminary techno-economic assessment (TEA) of a biorefinery coproducing ethanol, pyrolysis oil and char from Norway spruce (Picea abies) via steam explosion and enzymatic saccharification followed by anaerobic fermentation of the sugars, and fast pyrolysis of the lignin-rich saccharification residue. The capacity of the modelled biorefinery was set to treat 100,000 tons of dry wood per year. The input for the assessment of the facility was retrieved from process simulations carried out in COFE v3.6 (AmsterCHEM), see Note I. Here, we propose different strategies to minimize the total costs of the biorefinery. The results indicate that the studied biorefinery process is economically feasible, while its profitability depends considerably on the source of hydrogen, oscillation in the market price of the generated products and utility costs.